Effects of carbohydrate mouth rinse on cycling time trial performance: A systematic review and meta-analysis - Brietzke, C.; Franco-Alvarenga, P. E.; Coelho-Júnior, H. J.; Silveira, R.; Asano, R. Y.; Oliveira Pires, F. (Sports Medicine, 2019)
Background: Despite the growing number of studies reporting carbohydrate mouth rinse effects on endurance performance, no systematic and meta-analysis review has been conducted to elucidate the level of evidence of carbohydrate mouth rinse effects on cycling trial performance such as time-, work-, and distance-based trials. Objectives: The objective of this study were to establish the effect of a carbohydrate mouth rinse on cycling performance outcomes such as mean power output and time to complete a trial, together with the risk of bias in the cycling-carbohydrate mouth rinse literature. Methods: We systematically reviewed randomized placebo-controlled trials that assessed carbohydrate mouth rinse effects on mean power output and time to complete the trial. A random-effects meta-analysis assessed the standardized mean difference between carbohydrate and placebo mouth rinses. Results: Thirteen studies (16 trials) were qualitatively (systematic review) and quantitatively (meta-analysis) analyzed with regard to mean power output (n = 175) and time to complete the trial (n = 151). Overall, the reviewed studies showed a low risk of bias and homogeneous results for mean power output (I2 = 0%) and time to complete the trial (I2 = 0%). When compared with placebo, the carbohydrate mouth rinse improved mean power output (standardized mean difference = 0.25; 95% confidence interval 0.04-0.46; p = 0.02), but not the time to complete the trial (standardized mean difference = -?0.13; 95% confidence interval - 0.36 to 0.10; p = 0.25). Conclusion: The present systematic and meta-analytic review supports the notion that a carbohydrate mouth rinse has the potential to increase mean power output in cycling trials, despite showing no superiority over placebo in improving time to complete the trials. Electronic supplementary material: The online version of this article ( https://doi.org/10.1007/s40279-018-1029-7)